If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7-3x+8x=2
We move all terms to the left:
7-3x+8x-(2)=0
We add all the numbers together, and all the variables
5x+5=0
We move all terms containing x to the left, all other terms to the right
5x=-5
x=-5/5
x=-1
| q=16÷4 | | -16+11=h | | 4(x+6)+2(-x+6)=-10 | | 4x=27=75 | | 3x+6+2x-1=4x-5 | | p=4−-14 | | 9w=35+4w | | 11=-3+2q | | 7x+30+9x+42=90 | | 3=m+5/5 | | j=3−12 | | 5n+10n=15n | | 8(x+2)-2(3x+7)=-2 | | 6y+2=+14 | | 3=g{-4}-53=−4g−5 | | g=-13+11 | | 39=v/4+12 | | 2(c-16)=-8 | | 3(5x-2)+4x=0x+6-2x | | k=00.99 | | 6x/5+1=31 | | 99k=8 | | 2(t-4)=10-2+ | | h−5=5 | | z/2+7=−51 | | b−b+4b+3b−6b=13 | | f=10−1 | | 5n-4n=17 | | 5(2x+3)=3(4x1)-2(3x+2) | | 9+5=d | | 8-4÷2=x | | -1k-5k=5k-4 |